In times of Coronavirus: reflections about the pandemic and the possibilities from approaching the Sciences Teaching through the STS Education (Research, Society and Development, 2020)
Considering the pandemic context and its social implications, this work presents a theoretical-practical essay that objectifies discussing about the possibility of approaching the Coronavirus pandemic in the Sciences Teaching, starting off on the assumptions of the Science-Technology-Society Education. We elaborated this proposition at the emergencial context  from the Coronavirus, type Sars-Cov-2, pandemic that triggers the Covid-19 and is causing countless changes in every sector from the society, but its lethality that stands out, reaping thousands of lives around the globe and at Brazil. The political, economical and environmental dimensions approach at the development of certain subjects can contribute to a coherent teaching with a critical education concept. Therefore, four axis that converges in this theme approach were elaborated. Axis I concentrates possible information approach from the media about the pandemic, with Fake News been highlighted. Axis II embraces possibilities of health matters approach, and the possible relation with conceptual contents, thought for the interdisciplinary work.  Axis III comprises possible approaches referring to Science and Technology and its Social implications. Axis IV ends with an approach to issues related to the unveiled socioenvironmental crisis, that worsen inequalities. It’s concluded that the present proposition is a possibility of initiating educational practices compromised with a contextualized teaching, interdisciplinary and that a thematic approach favors the emerging social issues discussion, concerned with an effectively critical way of teaching.